Association between kidney disease index and decline in cognitive function with mediation by arterial stiffness in Asians with type 2 diabetes - Low, Serena (2024)
Background: Decline in renal function impairs systemic clearance of amyloid-β which characterizes Alzheimer's disease while albuminuria is associated with blood-brain barrier disruption due to endothelial damage. Arterial stiffness adversely affects the brain with high pulsatile flow damaging cerebral micro-vessels. Objective: To examine association between a novel kidney disease index (KDI), which is a composite index of estimated glomerular filtration (eGFR) and urinary albumin-To-creatinine ratio (uACR), and cognitive function with potential mediation by arterial stiffness. Methods: This was a longitudinal multi-center study of participants with type 2 diabetes (T2D) aged 45 years and above. We assessed cognitive function with Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Pulse wave velocity (PWV), an index of arterial stiffness, was measured using applanation tonometry method. KDI was calculated as geometric mean of 1/eGFR and natural logarithmically-Transformed (ln)(ACR∗100). Results: There were 1,303 participants with mean age 61.3±8.0 years. LnKDI was associated with lower baseline RBANS total score with adjusted coefficient-2.83 (95% CI-4.30 to-1.35; p<0.001). 590 participants were followed over up to 8.6 years. LnKDI was associated with lower follow-up RBANS score in total, immediate memory, visuo-spatial/construction and attention domains with corresponding adjusted coefficients-2.35 (95% CI-4.50 to-0.20; p=0.032),-2.93 (95% CI-5.84 to-0.02; p=0.049),-3.26 (95% CI-6.25 to-0.27; p=0.033) and-4.88 (95% CI-7.95 to-1.82; p=0.002). PWV accounted for 19.5% of association between and follow-up RBANS total score. Conclusions: KDI was associated with lower cognitive function globally, and in immediate memory, visuo-spatial/construction and attention domains. Arterial stiffness mediated the association between KDI and cognitive decline in patients with T2D.